2009
DOI: 10.1007/s11661-009-0051-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Grain Boundary Character on Creep Void Formation in Alloy 617

Abstract: Alloy 617, a high temperature creep-resistant, nickel-based alloy, is being considered for the primary heat exchanger for the Next Generation Nuclear Plant (NGNP) which will operate at temperatures exceeding 760 o C. Orientation imaging microscopy (OIM) is used to characterize the grain boundaries in the vicinity of creep voids that develop during high temperature creep tests (800-1000 o C at creep stresses ranging from 20-85 MPa) terminated at creep strains ranging from 5-40%. Observations using optical micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…Recent work by Lillo et al suggested that significant creep cavitation did not occur in Alloy 617 until greater than 10% creep strain during creep deformation at 900°C and 1000°C (15). In the present work, cavities were not observed in any of the creep-fatigue specimens tested at 950°C with hold times as long as 1800 sec.…”
Section: Al Oxidesupporting
confidence: 43%
“…Recent work by Lillo et al suggested that significant creep cavitation did not occur in Alloy 617 until greater than 10% creep strain during creep deformation at 900°C and 1000°C (15). In the present work, cavities were not observed in any of the creep-fatigue specimens tested at 950°C with hold times as long as 1800 sec.…”
Section: Al Oxidesupporting
confidence: 43%
“…During the constant load uniaxial creep testing at 900°C and 1000°C, creep cavitation did not occur in Alloy 617 until greater than ~10% creep strain [6]. Very limited cavity formation is observed in this alloy and a critical amount of creep deformation is required before creep cavities nucleate.…”
Section: Vib Creepmentioning
confidence: 87%
“…[6] Specimens had a 4.2 mm diameter and 16.6 mm gage length resulting in a gage length to diameter ratio of 4.0. The creep temperature was controlled to within ±3°C of the target creep temperature.…”
Section: Ivc Creep Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been further shown that voids form along the grain boundaries of high resolved tensile and shear stress, frequently accompanied by a high population of carbides (Lillo et al, 2009). It is easily imagined that a large fraction of the grain boundaries in a multiaxially loaded system satisfies these criteria for carbide redistribution and void formation.…”
Section: Discussionmentioning
confidence: 99%